2022
DOI: 10.1111/joa.13657
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of neurocranial size and shape across varied lab mouse populations

Abstract: Brain and skull tissues interact through molecular signalling and mechanical forces during head development, leading to a strong correlation between the neurocranium and the external brain surface. Therefore, when brain tissue is unavailable, neurocranial endocasts are often used to approximate brain size and shape. Evolutionary changes in brain morphology may have resulted in secondary changes to neurocranial morphology, but the developmental and genetic processes underlying this relationship are not well und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 100 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Growth of the brain and cranium are dynamic and intimately integrated through common molecular signaling pathways and responsiveness to mechanical forces to ensure an appropriately snug fit. 66 , 67 For example, the growing brain generates tensile strain on the developing cranial bones, which promotes bone remodeling to accommodate the expanding neural tissue. 68 This relationship is well represented by cases of hydrocephalus, in which excess CSF results in abnormal pressure within the cranial vault.…”
Section: Individual Variability In Calvarial Thicknessmentioning
confidence: 99%
“…Growth of the brain and cranium are dynamic and intimately integrated through common molecular signaling pathways and responsiveness to mechanical forces to ensure an appropriately snug fit. 66 , 67 For example, the growing brain generates tensile strain on the developing cranial bones, which promotes bone remodeling to accommodate the expanding neural tissue. 68 This relationship is well represented by cases of hydrocephalus, in which excess CSF results in abnormal pressure within the cranial vault.…”
Section: Individual Variability In Calvarial Thicknessmentioning
confidence: 99%
“…Another recent mouse study has identified a locus on chromosome 1 linked to AKT3 expression and brain size, which also appears to translate into neurocranial variations via structural interactions (Percival et al, 2022). Interestingly, computational simulations imply that simple plastic deformation coupled with ontogenetic variations of tissue compliance (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate genome‐wide association analysis suggests that neural crest‐derived components of the cranium respond to brain growth via local paracrine signalling, which is driven by physical interactions (Naqvi et al, 2021). Another recent mouse study has identified a locus on chromosome 1 linked to AKT3 expression and brain size, which also appears to translate into neurocranial variations via structural interactions (Percival et al, 2022). Interestingly, computational simulations imply that simple plastic deformation coupled with ontogenetic variations of tissue compliance (i.e.…”
Section: Introductionmentioning
confidence: 99%